Adolescent Fertility in Selected States of India - Suresh Sharma (Population Research Center Institute of Economic Growth, 2003)
The consistently high rate of adolescent childbearing in India is an issue of concern to policy makers because of the serious negative social, economic and health consequences associated with early pregnancy. Besides, early marriage leads to the beginning of childbearing at an early age, which eventually increases the risk of mortality and morbidity for both mother and child. The specific objective of this study is to analyze the role of proximate determinants in explaining variations in adolescent fertility in selected states of India. The data for the study is drawn from National Family Health Survey-2 (NFHS-2) in 1998-99. In addition, the information obtained from Censuses and Sample Registration System (SRS) is also utilized in the study. The Overall proportion of adolescent mothers in total married adolescents has declined. Among proximate determinants it is found that age at marriage and use of contraception play significant role in explaining adolescent fertility differentials. The proportion married among adolescents is much higher in northern states than southern states. Post Partm Aamenorrhhea (PPA) period is longer in West Bengal and comparably shorter in Kerala and Uttar Pradesh. However, Post Partum Amenorrhhea (PPA) differentials don't seem to play any significant role in explaining adolescent fertility differentials.